Transcatheter Arterial Embolization (TAE) for Zygoma Malignant Epithelial Tumor: A Case Report - Manginstar, Christian; Merung, Marselus; Saleh, Denny; Rimporok, Samuel (Medical Scope Journal, 2025)
Abstract: Malignant epithelial tumors of the zygoma are rare and difficult to manage. Treatment options include surgery, radiotherapy, and chemotherapy. The primary indication for transarterial embolisation (TAE) involved the selective delivery of embolic agents via a catheter into the blood vessels supplying the tumor, leading to ischemia and subsequent tumor necrosis. This study aimed to evaluate the effectiveness and safety of TAE therapy in managing malignant epithelial tumors of the zygoma. We reported a 64-year-old female presented with an 8-month history of a progressively larger and ulcerated mass on the left zygoma, accompanied by pain. Previous FNAB examination in 2023 confirmed a malignant epithelial tumor. Physical examination revealed a fragile mass measuring 10x8 cm. The patient underwent TAE, resulting in significant tumor reduction. After TAE, the patient showed significant clinical improvement. Pain was reduced, and the tumor size was markedly reduced. Ulceration on the tumor surface also began to improve. A few days after TAE, the patient was discharged in stable condition. At the follow-up evaluation one month later, the tumor size continued to reduce, and there were no signs of recurrence. In conclusion, transcatheter arterial embolization is a promising therapeutic modality for managing malignant epithelial tumors in the cheek, especially in inoperable cases or as palliative therapy. This case report provides additional evidence regarding TAE's effectiveness and safety in managing malignant epithelial tumors. Further studies with a larger number of patients are needed to confirm these findings and determine TAE's role in the comprehensive management algorithm of malignant epithelial tumors. Keywords: malignant epithelial tumor; transcatheter arterial embolization